A theoretical justification for the study of skin sensitivity in patients with bell's palsy (2008)
The purpose of this review is to highlight the importance of conducting studies to estimate the level of association between measures of skin sensitivity, facial region, facial paralysis level, and time of evolution, in patients with Bell's palsy; the above stems from the theoretical review of various studies that have found differences in measures of pressure threshold, two-point discrimination and appreciation of the vibration between different facial regions, both in patients with this kind of palsy, as in healthy people. It was also suggested to determine the level of correlation between these measures. Consistent with the studies reviewed, it is proposed that the records are made in regions innervated by the facial nerve supraorbital, infraorbital, inferior alveolar mental and headset. On the other hand, it is recommended to follow one of the classic psychophysical methods for measuring threshold to pressure and discrimination of two points, the choice of method will be done according to the instrument, the tactile quality and some specific aspects of skin sensitivity.